Significant Improvement in Survival After Allogeneic Hematopoietic Cell Transplantation During a Period of Significantly Increased Use, Older Recipient Age, and Use of Unrelated Donors - Theresa Hahn; Philip L. McCarthy; Anna Hassebroek; Christopher Bredeson; James Gajewski; Gregory A. Hale; Luis Isola; Hillard M. Lazarus; Stephanie J. Lee; Charles F. LeMaistre; Fausto R. Loberiza; Richard T. Maziarz; et al. (2013)
Over the past four decades, allogeneic hematopoietic cell transplantation (alloHCT) has evolved as a curative modality for patients with hematologic diseases. This study describes changes in use, technique, and survival in a population-based cohort.The study included 38,060 patients with hematologic malignancies or disorders who underwent first alloHCT in a US or Canadian center from 1994 to 2005 and were reported to the Center for International Blood and Marrow Transplant Research.AlloHCT as treatment for acute lymphoblastic (ALL) and myeloid leukemias (AML), myelodysplastic syndrome (MDS), and Hodgkin and non-Hodgkin lymphomas increased by 45%, from 2,520 to 3,668 patients annually. From 1994 to 2005, use of both peripheral (7% to 63%) [corrected] and cord blood increased (2% to 10%), whereas use of marrow decreased (90% to 27%). Despite a median age increase from 33 to 40 years and 165% [corrected] increase in unrelated donors for alloHCT, overall survival (OS) at day 100 significantly improved for patients with AML in first complete remission after myeloablative sibling alloHCT (85% to 94%; P < .001) and unrelated alloHCT (63% to 86%; P < .001); 1-year OS improved among those undergoing unrelated alloHCT (48% to 63%; P = .003) but not among those undergoing sibling alloHCT. Similar results were seen for ALL and MDS. Day-100 OS after cord blood alloHCT improved significantly from 60% to 78% (P < .001) for AML, ALL, MDS, and chronic myeloid leukemia. Use of reduced-intensity regimens increased, yielding OS rates similar to those of myeloablative regimens.Survival for those undergoing alloHCT has significantly improved over time. However, new approaches are needed to further improve 1-year OS.